IMPLEMENTASI METODE COOPERATIVE TIPE JIGSAW DALAM MENINGKATKAN KEMAMPUAN MENULIS TEKS PROSEDUR SISWA KELAS VII SMP - Baiq Yuliatin Ihsani; Dewi Permata Sari; Lina Wahyuni; Etta Atteta; Rina Rahmatina Dita; Nur Sakinah Yearham; Marina Marina; Muhammad Yusuf (JURNAL EDUCATION AND DEVELOPMENT, 2024)
This research aims to find out how the Cooperative Jigsaw Type Method is implemented in improving the ability of VII Class Junior High School students to write procedural text. The research subjects consisted of 32 students in class VII-F of SMP Negeri 10 Mataram for the academic year 2023-2024, with 18 male students and 14 female students. Problems arise due to students' low ability to write, so problems are found regarding writing ability so that sampling as research subjects is carried out with purposive sampling. This research was conducted using the Classroom Action Research (PTK) approach.The instruments used are tests and student worksheets. The research uses a score of 75 as the minimum completeness criterion. The research results showed that in the pre-cycle the completeness result was 56%, in the first cycle the result was 62% and in the second cycle it was 77%. It is hoped that the results of this research can be used as a reference by teachers in schools to apply the Cooperative Jigsaw Type Method in Improving the Ability to Write Procedure Texts for Grade VII Middle School.